When plague strikes : the Black Death, smallpox, AIDS - Giblin, James Cross 1933-2016; Frampton, David (New York : Scholastic, 1995)
Compassionate and arresting, this exploration of three major diseases that have changed the course of history--the bubonic plague, smallpox, and AIDS--chronicles their fearsome death toll, their lasting social, economic, and political implications, and how medical knowledge and treatments have advanced as a result of the crises they have occasioned.
Z
1190
Z
Keywords: Plague -- History -- Juvenile literature; Smallpox -- History -- Juvenile literature; AIDS (Disease) -- History -- Juvenile literature; Plague -- History; Smallpox -- History; AIDS (Disease) -- History; Epidemics -- History; Diseases -- History